UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN ADAB PESERTA DIDIK - Permatasari, Eka Wahyu Dian; Ali, Mohamad (PAI RAFAH, 2023)
This study aims to determine the efforts of Islamic Religious Education Teachers in improving students' manners at SMK Batik 2 Surakarta. What will be revealed in this study is the efforts of Islamic religious education teachers to improve student morals. In addition, it aims to find out the inhibiting factors or challenges experienced by teachers in improving student morals. According to the type, this research is qualitative research. This research is located at SMK Batik 2 Surakarta, with the research subject being the Islamic religious education teacher at SMK Batik 2 Surakarta. The methods used in data collection techniques are interviews, observation, and documentation. The stages used in analyzing the data are data reduction, data display, and conclusion drawing or verification. With this method, it is expected to obtain concrete data and in accordance with the needs of research conducted at SMK Batik 2 Surakarta. The results showed that: (1) the efforts of Islamic religious education teachers in improving student morals include: (a) increasing discipline (b) crafts (c) reducing gadgets, (d) adding insight into religion. (2) the inhibiting factors of Islamic religious education teachers in improving student morals at SMK Batik 2 Surakarta, namely especially from gadgets/cellphones have a strong influence. Actually, it is an appropriate and sophisticated communication tool, but young people now often misuse these gadgets. Then because of the differences in character because the characters of the students are different, maybe that is a very influential factor in this digital era. As for the factor of the lack of religious knowledge, it is very minimal so that the adab of the students is lost.